Anxiety and Depression in Hypertensive Women: Influence on Symptoms and Alexithymia - Beatriz Rueda; Alemán JF (Archives of Clinical Hypertension - Peertechz Publications, 2015)
Objectives: Depression and anxiety are common mental disorders in women with cardiovascular disease. However, little research has examined the role of these disorders among women suffering from essential hypertension (EH). The present study explored the prevalence of both depression and anxiety in women with hypertension. It also examined the relationships of depression and anxiety with the frequency and severity of physical symptoms, alexithymia and the dimensions of difficulty in identifying and describing feelings (DIF and DDF). Method: The sample consisted of 111 women (mean age= 58 years) who attended a health care center to control their hypertension. Participants completed the Hospital Anxiety and Depression Scale (HADS), a checklist of physical symptoms and the Twenty-Item Toronto Alexithymia Scale (TAS-20). Results: The prevalence of anxiety was higher (65%) than the prevalence of depression (30%). Bivariate correlations showed that depression and anxiety were associated with more frequent and greater levels of physical symptoms, and more alexithymia. In multiple regression analyses, only anxiety positively predicted the frequency and severity of the symptoms, and the dimensions of DIFand DDF. However, with respect to total alexithymia, both depression and anxiety emerged as positive and independent predictors. Conclusions: The results highlight the importance of detecting anxiety disorders in women with EH due to their high prevalence. They also provide evidence of the independent role that both depressive and anxiety disorders can play when predicting alexithymia in these patients.